Area-Wide Control Program in Management of Chinese Citrus Fly, Bactrocera minax (Enderlein) (Diptera: Tephritidae), in Citrus Orchards, Sindhuli, Nepal - Adhikari, D.; Thapa, R.B.; Joshi, S.L.; Du, J.J. (Journal of Agriculture and Environment, 2021)
Chinese citrus fly, Bactrocera minax (Enderlein) (Diptera: Tephritidae) is one of the important citrus pests in Nepal, India and Bhutan including China where it was originated. Since 2014/15, the problem of B. minax in sweet orange fruit is being faced by citrus growers in Sindhuli, Nepal. To mitigate the problem of B. minax, Chinese citrus fly in the orchards, afield practice of area wide control program (AWCP) was piloted in the selected 231 citrus orchards for the first time in Sindhuli in 2018 which has been adopted by 1153 citrus growers in 2019. The obvious recessions of mean fruit damage percentages due to B. minax in the sweet orange orchards at different locations in 2018 (range: 3.9 ± 1.1% to 29.7 ± 9.6%) and 2019 (range: 2.6 ± 0.8% to 7.5 ± 2.3%) have been achieved by virtue of B. minax management through AWCP with poisonous protein bait component and sanitation measure in the citrus orchards.